Strategic Fit of Solar Power Solutions for a Non-Electricity- Producing Company A Case Study of Liseberg AB - Fredriksson, Elin; Haglund, Stina (My University, 2023)
The escalating impacts of climate change necessitate societal action to transition towards a decarbonised economy. In this green transition, electrification of society is a critical component which implies more renewable electricity in the grid resulting in a more volatile electricity market. For Non-Electricity-Producing (NEP) companies, the importance of implementing new ways of strategically managing electricity supply becomes apparent. Solar power is one of several renewable electricity production methods, which is assessed as being suitable for NEP companies, both because of its relatively low cost, and its flexible applications. However, little guidance exists for NEP companies wanting to integrate solar power into their electricity supply. This pertains specifically to the strategic fit of various solar power solutions with their current business operations. To this end, this thesis sets out to, through a single-case study, first, identify available solar power solutions for NEP companies to incorporate, and second, provide guidance regarding strategic fit between the solutions and the NEP company. Hence, the strategic fit analysis examines how well a new element (the solar power solution) fits with the NEP company, considering both an internal dimension, consisting of vertical and horizontal strategic fit, and an external dimension of strategic fit. To truly understand the strategic dimensions and the culture of the case company, and what solar power solutions that exist in their vicinity, a qualitative case study was carried through. This qualitative case study was based on semi-structured interviews with 10 employees from different functions at the case company and secondary data such as websites, market reports and internal documents. Further, a solution by solution approach to analyse each solar power solution’s strategic fit to the case company was made. We identified four main solar power solutions: Host-Owned, Power Purchase Agreement (PPA), Shared Solar, and Guarantees of Origin (GOs). Out of these four solutions, PPA and Shared Solar displayed the highest degree of strategic fit to the studied NEP company. The findings offer valuable insights for NEP companies planning to incorporate solar power, emphasising that a strategic fit analysis could serve as good guidance for decision-making. The analysis further reveals that the vertical and external dimensions of strategic fit seem to play a crucial role in determining if solar power is a good fit for the NEP company. The horizontal fit, however, seems to be of higher value when determining which of the available solutions to incorporate.
Keywords: solar photovoltaics; solar power; strategic fit; non-electricity-producing (NEP) company